Impact of Thin Meconium on Delivery and Early Neonatal Outcomes - Hanoch Schreiber; Adi Shilony; Reut Batia Amrami; Gal Cohen; Ofer Markovitch; Tal Biron-Shental; Sofia Bauer-Rusek; Shmuel Arnon; Michal Kovo (MDPI AG, 2023)
Several reports regarding the effects of thin meconium on maternal and neonatal outcomes are contradictory. This study evaluated the risk factors and obstetrical outcomes during deliveries complicated with thin meconium. This retrospective cohort study included all women with a singleton pregnancy, who underwent trial of labor >24 weeks of gestation, in a single tertiary center, over a six-year period. Obstetrical, delivery, and neonatal outcomes were compared between deliveries with thin meconium (thin meconium group) to deliveries with clear amniotic fluid (control group). Included in the study were 31,536 deliveries. Among them 1946 (6.2%) were in the thin meconium group and 29,590 (93.8%) were controls. Meconium aspiration syndrome was diagnosed in eight neonates in the thin meconium group and in none of the controls (0.41%, p < 0.001). In multivariate logistic regression analysis, the following adverse outcomes were found to be independently associated with increased odds ratio (OR) for thin meconium: intrapartum fever (OR 1.37, 95% CI 1.1-1.7), instrumental delivery (OR 1.26, 95% CI 1.09-1.46), cesarean delivery for non-reassuring fetal heart rate (OR 2.0, 95% CI 1.68-2.46), and respiratory distress requiring mechanical ventilation (OR 2.06, 95% CI 1.19-3.56). Thin meconium was associated with adverse obstetrical, delivery, and neonatal outcomes that should receive extra neonatal care and alert the pediatrician.